Foot terrain impact modeling and motion performance research of hexapod robot based on passive elastic leg. (April 2020) - Liu, Y F; Su, B; Zhou, L; Gao, H B; Ding, L; Jiang, L; Zou, F Q; Ma, C Y
Abstract: In order to improve the performance of the multi-legged robot, the impact of foot-terrain is an important target to measure the performance of the robot. In order to ensure the compliance contact of foot-terrain for the legged robot, it is essential to add passive spring between the calf and foot. The mechanical structure makes the leg of hexapod robot retractable passive elastic structure. For multi-legged robots with passive elastic legs, the foot-terrain impact model is presented to measure the dynamic performance and provide theoretical support for the low impact force motion planning. The traditional planning method will cause additional impact for the switching case between the swing and stance phase. This paper presents a motion planning method that considers the deformable leg structure and impact performance. The experiments have been carried out, and the results have demonstrated the effectiveness of the foot terrain impact model and motion planning method in comparison with a conventional method.